Analisis Pencatatan Dan Penilaian Persediaan Barang Dagang Berdasarkan PSAK No.14 Pada PT. Arus Cipta Eriady - Sarwo Edi Wibowo, Raudatul Islamiah Elfreda Aplonia Lau 2 (EKONOMIA, 2021)
This study aims to determine and analyze the recording and valuation of merchandise inventory at PT. Arus Cipta Eriady in 2017 based on the provisions in the Statement of Financial Accounting Standards (PSAK) No. 14 about supplies. With the formulation of the problem whether the method of recording and valuing merchandise inventory at PT. Arus Cipta Eriady in 2017 is in accordance with the provisions in the Statement of Financial Accounting Standards (PSAK) No. 14 about suppliesThe analytical tool used in this research is the Statement of Financial Accounting Standards (PSAK) No. 14 about supplies.The results of the analysis of the process of recording merchandise inventory at PT. Arus Cipta Eriady in 2017 is in accordance with the provisions in the Statement of Financial Accounting Standards (PSAK) No. 14 concerning inventories where the recording of merchandise inventory has been using the perpetual method. The results of the analysis of the valuation process of merchandise inventory at PT. Arus Cipta Eriady in 2017 is not in accordance with the provisions in the Statement of Financial Accounting Standards (PSAK) No. 14 concerning inventories where the valuation of merchandise inventory should be carried out using the First In First Out (MPKP) method or weighted average.